Beta‐diversity patterns elucidate mechanisms of alien plant invasion in mountains. Issue 4 (25th October 2012) - Marini, Lorenzo; Bertolli, Alessio; Bona, Enzo; Federici, Germano; Martini, Fabrizio; Prosser, Filippo; Bommarco, Riccardo
Abstract Aim Our aims were: (1) to separately evaluate the elevational patterns of β‐diversity for nestedness, species richness difference and replacement, (2) to identify the drivers of β‐diversity patterns by testing the effect of geographical and environmental distance (human population, temperature and land‐use), and (3) to compare the response on native versus alien species to elucidate mechanisms of community assembly along elevational gradients. Location Two mountain regions (Bergamo‐Brescia and Trento) in the Italian Alps. Methods We used two floristic datasets in which species composition was sampled within two regular grids. First, we extracted species elevational range and quantified species composition nestedness along the elevational gradient. Second, we partitioned β‐diversity into its species richness difference and replacement components and tested drivers using regression on distance matrix and hierarchical partitioning. All analyses were performed on natives and aliens, separately. Results For aliens, we found lack of mountain specialists (i.e. species with a distribution range restricted to high elevations), large nestedness, large species richness difference and low species replacement between low and high elevations. All findings point in the same direction: a great majority of alien species were introduced to the lowlands and only a subset of this community spread up the mountains. Both human pressures and temperature selection were important processes underpinning the observed filtering, while geographical and land‐use distances were not important. Natives present contrasting patterns with large replacement along the elevation gradients indicating different mechanisms of community assembly. Main conclusions The relatively large alien species replacement in the lowlands indicated the presence of a pool of species that may potentially invade the temperate mountains in the future. Investigations of the identity of alien species occurring in the lowlands and their climatic pre‐adaptation might provide tools to prevent invasions in the mountains by predicting the potential invaders and their future elevational distribution.